Lateral instability in a discharge channel. (June 2021) - Arrayás, M.; Fontelos, M.A.
Abstract: In this paper we study the lateral instability in a discharge channel using a continuum model. We observe analogies with the onset of Kelvin-Helmholz instability in fluids. In strong electric fields, lateral long wave length perturbations can grow while small wave length perturbations diminish during the discharge evolution. We perform numerical simulations and carry out asymptotic analysis of the instability.